Aircraft Components Maintenance Shop Production Planning Random Events Prioritization - Santos, Jorge (2014)
TAP Maintenance & Engineering (TAP M&E) is responsible for the maintenance and repair of aircraft components. Components with and without Customer Required Dates (CRDs) are distributed among TAP M&E groups and their respective technicians based on the type of repair and on the technicians skills and workload. This procedure is currently done in an empirical manner based on the group leader’s past experience. This report addresses the following two problems, which were posed by TAP M&E during the 81st European Study Group with Industry, with the aim of improving the currently implemented assignment procedure: (1) To prioritize the randomly arriving aircraft components. (2) To optimally distribute and schedule the repairs of the components amongst the technicians of the repair groups. An estimation formula for the CRDs of components that do not have one preassigned is proposed and used to prioritize the list of repairs. The importance of selecting good estimators for the interarrival times between repair requests, the turn-around-times and the man hours for repairs is discussed. In addition, a model for the assignment and scheduling problem is designed and a preliminary algorithm along with a numerical illustration is presented.